Analysis of ChatGPT and Gemini Mental Models of Apparent Motion of the Sun and Stars - Nurhikma Safitri; Jusman Mansyur; Haeruddin Haeruddin; Nurul Kami Sani; Andi Ulfah Khuzaimah (Koordinat Jurnal MIPA, 2026)
mental models regarding the apparent motion of the Sun and stars. The method used is a qualitative approach with an exploratory descriptive study using the reflective thematic analysis method according to Braun, Clarke, and Rance (2014). The subjects of this study were ChatGPT and Gemini, who also acted as respondents. The instrument used was 10 multiple-choice questions about the apparent motion of celestial bodies. Each answer was analyzed thematically to identify reasoning patterns, conceptual structures, and conformity with scientific mental models. The results show that ChatGPT predominantly displays a scientific mental model consistent with a heliocentric understanding and scientific explanation of apparent motion, while Gemini tends to display a hybrid mental model with a mixture of scientific concepts and preconceptions. The comparison of the two shows differences in conceptual depth, consistency of reasoning, and accuracy of scientific representation. These findings contribute to the development of the study of artificial intelligence mental models and open up opportunities for their use in AI-based science learning